Sexual activity in terms of cardiac rehabilitation after cardiovascular incidents - Grudzińska, Aleksandra; Dudzińska, Paulina; Milanowska, Małgorzata; Jarosz, Dominika; Tsitko, Hanna (Journal of Education, Health and Sport, 2023)
Cardiovascular diseases (CVD) are still the leading cause of death. Environmental factors such as smoking, low physical activity and poor diet have the greatest impact on the incidence of the disease. For patients after a cardiovascular incident, cardiac rehabilitation is the key to recovery. One possible path of rehabilitation is sexual activity (SA). Sexual activities are similar to mild/moderate physical activity during a short period. Most patients are recommended to involve in sexual activity after prior comprehensive evaluation of physical condition. Before involving in sexual activity the general condition of the patient needs to be checked. A useful method for this is a stress testing. The patients with stable cardiac symptoms and good functional capacity are at a low risk of recurrent cardiovascular events, and others require treatment or improvement of heart function. The most efficient way to provide SA is a sexual counseling. Evidence suggests that relatively few cardiac patients receive sexual counseling, which can result in negative outcomes ranging from psychological, physical, and quality of life. Sexual problems and concerns are prevalent, including patient and partner fear of causing another heart attack. It is because people still believe that sexual activity is too risky and they cease all of it. Sexual counseling is needed across health care settings to ensure that patients receive information to safely resume SA.